Pengaturan Anti-Terorisme dalam Hukum Positif Indonesia dan Hukum Pidana Islam: Suatu Studi Perbandingan - Zulfahmi; Dina Dwi Anggraini (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Terrorism is a global threat considered illegal under various legal systems, including in Indonesia. The country has faced several acts of terrorism that threaten national peace and security. This study aims to compare anti-terrorism regulations in Indonesian positive law and Islamic criminal law, as well as to evaluate the effectiveness of both. The research method used is normative legal research with a comparative approach, analyzing the similarities and differences in regulations, implementation, and effectiveness of anti-terrorism policies between the two legal systems. The results show that both Indonesian positive law and Islamic criminal law consider terrorism as a serious crime. Indonesian positive law, through Law No. 5 of 2018, provides a comprehensive legal framework with a focus on prevention and enforcement. Meanwhile, Islamic criminal law regards terrorism as jarimah hirabah with severe punishments according to the level of seriousness. The evaluation indicates the need for strengthened institutional coordination, legislative revisions, and enhancement of deradicalization programs and public education.